Cimetidine as a free radical scavenger - Lambat, Zaynab Yusuf (Rhodes University, Faculty of Pharmacy, Pharmacy, 2003)
The present study was undertaken to determine the effects and possible mechanism of action of cimetidine in cancer and Alzheimer's disease (AD). Throughout this study emphasis is placed on free radical levels since the magnitude of the relationship between diseases and the levels of free radicals vary from one disease to another. Studies were carried out to examine the effect of cimetidine on free radical levels using superoxide formation and lipid peroxidation as indicators of free radical levels. The experiments revealed that addition of cimetidine, especially in high concentrations (0.5 and 1.0 x10-6 M) significantly inhibited WHCO6 cancer cell growth rather than cancer cell growth, as no normal control was available. Free radical formation as well as hydroxyl radical formation were reduced in the deoxyribose assay. In addition, cimetidine exhibits properties of binding to metals such as copper and iron. To maintain consistency in the experiments, a WHCO6 (Wits Human Carcinoma of the Oesophagus) cell line was used to investigate the effect of cimetidine in cancer. Neurodegeneration was induced in the rat brain using neurotoxins such as cyanide to investigate the relationship between cimetidine in AD. A decrease in cancer cell growth was accompanied by a concomitant decrease in the levels of free radicals and lipid peroxidation, suggesting that the growth-inhibitory effects of cimetidine on WHCO6 cancer cells in vitro may be due to free radical scavenging properties. This proposal was further strengthened by determination of free radical levels in the rat brain. After treatment with neurotoxins to induce neurodegeneration, the levels of free radicals in the rat brain suggest that addition of cimetidine reduces free radical levels in the rat brain in a dosedependent manner. Further experiments were done in an attempt to uncover the underlying mechanism by which cimetidine exhibits free radical scavenging properties. Metal binding studies were done using electrochemical, HPLC and UV/Vis studies. The results show that cimetidine binds iron and copper. These metals have been implicated in free radical production via the Fenton reaction. By binding with cimetidine the metals become unavailable to produce free radicals and hence cimetidine indirectly reduces the formation of free radicals. The final experiment was the determination of cimetidine as a hydroxyl radical scavenger in the deoxyribose assay. Cimetidine was shown to act as a potent hydroxyl radical scavenger, thereby confirming its activity as a free radical scavenger. In addition, cimetidine protects against damage to the deoxyribose sugar, a component of DNA. Whilst there are many theories that explain the therapeutic role of cimetidine in degenerative disease, the actual mechanism of the role of cimetidine is emphasized as a free radical scavenger. Regardless of the mechanism of action, cimetidine does inhibit tumour growth according to this study and also reduce free radical levels in neurodegeneration, which suggests a role for cimetidine as a possible additive in treatment of patients with such disease states. These findings have important clinical implications, and needs to be investigated further.
Keywords: Cimetidine; Cimetidine -- Physiological effect; Cimetidine -- Therapeutic use; Alzheimer's disease -- Treatment; Cancer -- Treatment; Free radicals (Chemistry) -- Physiological effect